Instabilities constraint and relativistic mean field parametrization - Sulaksono, A.; Kasmudin; Bürvenich, T. J.; Reinhard, Paul-Gerhard; Maruhn, J. A. (International Journal of Modern Physics E-Nuclear Physics, 2011)
Two parameter sets (Set 1 and Set 2) of the standard relativistic mean field (RMF) model plus additional vector isoscalar nonlinear term, which are constrained by a set of criteria20 determined by symmetric nuclear matter stabilities at high densities due to longitudinal and transversal particlehole excitation modes are investigated. In the latter parameter set, δ meson and isoscalar as well as isovector tensor contributions are included. The effects in selected finite nuclei and nuclear matter properties predicted by both parameter sets are systematically studied and compared with the ones predicted by well-known RMF parameter sets. The vector isoscalar nonlinear term addition and instability constraints have reasonably good effects in the high-density properties of the isoscalar sector of nuclear matter and certain finite nuclei properties. However, even though the δ meson and isovector tensor are included, the incompatibility with the constraints from some experimental data in certain nuclear properties at saturation point and the excessive stiffness of the isovector nuclear matter equation of state at high densities as well as the incorrect isotonic trend in binding the energies of finite nuclei are still encountered. It is shown that the problem may be remedied if we introduce additional nonlinear terms not only in the isovector but also in the isoscalar vectors. © 2011 World Scientific Publishing Company.
CRIS-Team Scopus Importer:2023-07-24
Keywords: nuclear matter; Nuclear structure; relativistic mean field